Efeito de um protocolo domiciliar de fisioterapia pélvica em mulheres com vulvodínia: uma série de casos - SOUSA, Ana Beatríz Coutinho (2022)
INTRODUCTION: Vulvodynia is defined as “vulvar pain, with at least 3 months of duration, in the absence of a clearly identifiable cause, which may have potential associated factors”. OBJECTIVE: To evaluate the response of sexual function in women with vulvodynia after a home physical therapy protocol. MATERIALS AND METHODS: This is a case series study, in which 6 women aged between 22 and 61 years, with symptoms of vulvodynia participated. The patients' sexual function and pain were assessed using the Female Sexual Function Index (FSFI) and McGill-Melzack Pain Questionnaire (SF-MPQ) questionnaires, before and after physical therapy intervention. Data were stored in Excel and, based on that, statistical analysis was performed using the paired t-test. RESULTS: The mean FSFI score before treatment was 16.9 and after treatment it was 20.98, with an increase of 5.42% in the mean of the final score, showing an improvement in sexual function. In the McGill-Melzack Pain Questionnaire, a decrease in the score before and after treatment was observed, from 37.83 to 21.83, a reduction of 42%. CONCLUSION: A home pelvic physical therapy protocol demonstrates improvement in sexual function in women with vulvodynia.